2016
DOI: 10.3390/su8070669
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of the Nutrient Removal Performance of a Gross Pollutant Trap (GPT) in Australia

Abstract: Field testing of a proprietary stormwater treatment device (GPT) was undertaken over a one year period at a commercial site located in Sippy Downs, Queensland. The focus of the study was primarily on evaluating the effectiveness of the GPT device in removing pollution in the form of nutrients (Total Suspended Solids, Total Nitrogen, Total Phosphorus) from stormwater runoff. Water quality analysis was performed on water samples taken from the inflow and outflow of the GPT during 15 natural rainfall events. A ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The mean value of collection efficiencies was evaluated to be 29% for TSS, 40% for TP, 11% for TN, 6% for THM, and 20% for hydrocarbons [10]. In [12], field testing of a gross pollutant trap (GPT) was undertaken over a period of two years at a commercial site located in Queensland, Australia. Approximately 85% of the total catchment area was impervious.…”
Section: Summary Of the Ecosol Litter Basket Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The mean value of collection efficiencies was evaluated to be 29% for TSS, 40% for TP, 11% for TN, 6% for THM, and 20% for hydrocarbons [10]. In [12], field testing of a gross pollutant trap (GPT) was undertaken over a period of two years at a commercial site located in Queensland, Australia. Approximately 85% of the total catchment area was impervious.…”
Section: Summary Of the Ecosol Litter Basket Performancementioning
confidence: 99%
“…The catchment contained only residential land use [11]. Field testing of a gross pollutant trap (GPT) was also undertaken over a period of two years at a commercial site located in Queensland, Australia [12]. The catchment drainage area consisted of sealed car parks (50%), building roofs (35%), and approximately 15% open space containing lawns and intermittent impervious paved surfaces (concrete pathways).…”
Section: Introductionmentioning
confidence: 99%
“…A study made by Nichols and Lucke [14] who used manufactured GPT (Humegard ® ) showed removal of TP, TN and TSS even though the values did not meet the water quality requirement as shown in Table 1. A combination of BMPs such as GPT, bio-retention and pond has been done by Sahrma et al [16] increased the removal of TSS, but it requires extra space and costly due to the multiple installations of BMPs.…”
Section: Performance Of Gpts Embedded With Adsorbents In Dissolved Pollutants Removalmentioning
confidence: 99%